(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2022)
In the present article we show the relationship that Rama establish between language/power and space/power in the Ciudad Letrada. This new paradigm has allowed us to think and rethink Latin American literature and cultural studies, non the less, it also brings out contradictions inside the own thinking of the Uruguayan author. The strong division that the author establishes between the real city and the literate city does not allow one to think of the role of literature outside the field of institutionalized power, at the same time that he relegates the ontological reality of the latter to a merely instrumental one. Our proposal is to read this opposition in the light of the notion of transculturation, establishing a dialectic that allows us to consider the very policy of the real city and its active role in the expression of a political resistance literature.